Carbon cloth loaded vertical graphene / Ta2O5 composite electrode and preparation method thereof

By depositing Ta2O5 on the atomic layer on the carbon cloth, vertical graphene/Ta2O5 composite electrode material was prepared, which solved the problem of limited application of carbon cloth in the electrochemistry field, and achieved the effect of high electrochemical active area and low background current.

CN119530757APending Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703883.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The application of carbon cloth in the electrochemistry field is limited by its low electrochemical activity, small specific surface area and poor porosity, making it difficult to directly use as a high-performance electrode material.

Method used

Ta2O5 of different thicknesses were deposited on the surface of the carbon cloth loaded with vertical graphene by atomic layer deposition method, and vertical graphene/Ta2O5 composite electrode material was prepared.

Benefits of technology

The electrochemical active area of ​​the composite electrode is significantly improved, the background current is reduced, the electrochemical performance is improved, and the electrochemical characteristics are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005154059670000011
    Figure HDA0005154059670000011
  • Figure HDA0005154059670000012
    Figure HDA0005154059670000012
  • Figure HDA0005154059670000021
    Figure HDA0005154059670000021
Patent Text Reader

Abstract

The invention discloses a carbon cloth loaded vertical graphene / Ta2O5 composite electrode and a preparation method thereof.The composite electrode is obtained by depositing Ta2O5 on the surface of carbon cloth containing vertical graphene through atomic layer deposition equipment, the composite electrode has low background current and extremely high electrochemical active area and is excellent in electrochemical performance, and the preparation method is easy and convenient to operate and suitable for industrial production. The safety coefficient is high, the process is simple, and the composite electrode can be prepared through one-step operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon cloth-supported vertical graphene / Ta2O5 composite electrode and a preparation method thereof Background Art

[0002] Carbon nanomaterials, such as porous carbon, onion carbon, carbon nanotubes, graphene, etc., are common choices for electrode materials because they have great advantages in electrochemistry due to their high conductivity, large surface area, chemical stability, long cycle life and low cost. However, the electrochemical performance of carbon nanomaterials is not only affected by factors such as the structure and composition of the material, but also by the surface properties. Therefore, how to improve the electrochemical performance of carbon nanomaterials has become a hot topic in current research. Introducing heteroatoms or surface functional groups into carbon nanomaterials is one of the most effective ways to improve the electrochemical performance of carbon nanomaterials, because heteroatoms or surface oxygen groups in carbon nanomaterials can improve conductivity, thereby maximizing the electrochemical active area.

[0003] Carbon cloth is a highly conductive textile with good mechanical flexibility, light weight, and good chemical stability. It has great potential in the manufacture of flexible electrodes. However, due to its extremely poor electrochemical activity, small specific surface area, and poor porosity, carbon cloth is rarely used directly as an electrode material except as a current collector or for loading other capacitive materials. The most common role of carbon cloth in the field of electrochemistry is that it can provide a larger surface area after treatment, usually by functionalizing with heteroatoms, metals, hydrogen / oxides, nanoparticle carbon materials, or hybrid dopants to improve the electrochemical performance of the material.

[0004] Ta2O5 is an important transition metal oxide with high refractive index, high dielectric constant, wide band gap and other characteristics. Due to its excellent thermal and chemical properties, it has been widely used in new optoelectronic devices, electroluminescent devices, optical waveguides, optical films and other fields. It has been reported that Ta2O5 nanoparticles were synthesized by ionic liquid-assisted hydrothermal method, and then Ta2O5 reduced graphene oxide (Ta2O5-rGO) nanocomposites were synthesized by hydrothermal method for new non-intrinsic pseudocapacitive electrochemical lithium storage conversion negative electrode materials. It has been reported that Ta2O5 reduced graphene oxide (Ta2O5-rGO) composites were prepared by hydrothermal method for the detection of oxytetracycline. However, the hydrothermal method has some shortcomings, such as the difficulty in accurately controlling the loading amount of Ta2O5, the long preparation cycle, the reaction needs to be carried out at high temperature and high pressure, and the equipment requirements are high.

[0005] Atomic layer deposition (ALD), as a technology for preparing precious metals or metal oxides, has the following advantages over the hydrothermal method: the atomic layer deposition process can accurately control the thickness of the film at the atomic level; the temperature of the atomic layer deposition process is usually between 200°C and 300°C, which can be carried out at a lower temperature than the hydrothermal method, avoiding high temperature damage to the material; compared with the hydrothermal method, the preparation time is shorter, and a cycle process can be completed in about a few microseconds to a few hundred microseconds, greatly reducing the time cost.

[0006] The present invention adopts the atomic layer deposition method to deposit Ta2O5 of different thicknesses on the surface of the carbon cloth loaded with vertical graphene, and synthesizes the vertical graphene / Ta2O5 composite electrode material in one step. The composite electrode has good electrochemical performance, and its electrochemical active area is increased by about 15-22 times compared with the intrinsic vertical graphene carbon cloth material without Ta2O5 loading, and the background current is reduced. Summary of the invention

[0007] The object of the present invention is to provide an electrode material composed of vertical graphene / Ta2O5 composite and a preparation method thereof, wherein the electrode material has a large electrochemical active area and a low background current and exhibits excellent electrochemical properties.

[0008] The technical solution of the present invention is as follows:

[0009] A carbon cloth-supported vertical graphene / Ta2O5 composite electrode is obtained by depositing Ta2O5 on the surface of a carbon cloth containing vertical graphene using an atomic layer deposition device.

[0010] The preparation method of the carbon cloth-supported vertical graphene / Ta2O5 composite electrode of the present invention is as follows:

[0011] The carbon containing the vertical graphene is arranged on the sample stage of the atomic layer deposition equipment, the sample stage temperature is set to 250°C, and the sample stage preheating time is 35 minutes; the number of atomic layer deposition cycles is 1 to 40 times, and the residence time of the precursor tantalum source is 0.5s each time; after the deposition is completed, the composite electrode material is obtained;

[0012] in,

[0013] Carbon cloth containing standing graphene is commercially available;

[0014] The precursor tantalum source is tantalum methylethylamine.

[0015] The beneficial effects of the present invention are embodied in:

[0016] (1) The composite electrode prepared by the present invention has a low background current and a very high electrochemical active area;

[0017] (2) The preparation method of the present invention is easy to operate, has a high safety factor, and a simple process, and the preparation of the composite electrode can be achieved in one step. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : SEM image of vertical graphene.

[0019] Figure 2 : Raman spectrum of upright graphene.

[0020] Figure 3 : SEM image of Example 1 (vertical graphene carbon cloth ALD cycle 1 time).

[0021] Figure 4 : Raman image of Example 1 (vertical graphene carbon cloth ALD cycle 1 time).

[0022] Figure 5 : Potential window and background current curve of Example 1 (1 ALD cycle of vertical graphene carbon cloth).

[0023] Figure 6 Example 1 (1 ALD cycle of vertical graphene carbon cloth) in 1 mM Fe(CN)6 3- / 4- and cyclic voltammetry curves in 1M KCl solution.

[0024] Figure 7 : SEM image of Example 2 (vertical graphene carbon cloth ALD cycle 10 times).

[0025] Figure 8 : Raman spectrum of Example 2 (vertical graphene carbon cloth ALD cycle 10 times).

[0026] Fig. 9 : Potential window and background current curve of Example 2 (10 ALD cycles of vertical graphene carbon cloth).

[0027] Fig.10 Example 2 (10 ALD cycles of vertical graphene carbon cloth) in 1 mM Fe(CN)6 3- / 4- and cyclic voltammetry curves in 1M KCl solution.

[0028] Fig.11 : SEM image of Example 3 (vertical graphene carbon cloth ALD cycle 20 times).

[0029] Fig.12 : Raman spectrum of Example 3 (vertical graphene carbon cloth ALD cycle 20 times).

[0030] Fig.13: Potential window and background current curve of Example 3 (20 cycles of vertical graphene carbon cloth ALD).

[0031] Fig.14 Example 3 (20 ALD cycles of vertical graphene carbon cloth) in 1 mM Fe(CN)6 3- / 4- and cyclic voltammetry curves in 1M KCl solution.

[0032] Fig.15 : SEM image of Example 4 (vertical graphene carbon cloth ALD cycle 30 times).

[0033] Fig.16 : Raman spectrum of Example 4 (vertical graphene carbon cloth ALD cycle 30 times).

[0034] Fig.17 : Potential window and background current curve of Example 4 (vertical graphene carbon cloth ALD cycle 30 times).

[0035] Fig.18 Example 4 (30 ALD cycles of vertical graphene carbon cloth) in 1 mM Fe(CN)6 3- / 4- and cyclic voltammetry curves in 1M KCl solution.

[0036] Fig.19 : SEM image of Example 5 (vertical graphene carbon cloth ALD cycle 40 times).

[0037] Fig. 20 : Raman spectrum of Example 5 (40 ALD cycles of vertical graphene carbon cloth).

[0038] Fig.21 : Potential window and background current curve of Example 5 (40 cycles of vertical graphene carbon cloth ALD).

[0039] Fig. 22 Example 5 (40 ALD cycles of vertical graphene carbon cloth) in 1 mM Fe(CN)6 3- / 4- and cyclic voltammetry curves in 1M KCl solution. DETAILED DESCRIPTION

[0040] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0041] In the following embodiments,

[0042] The atomic layer deposition equipment was purchased from Shenzhen Yuansu Technology Co., Ltd., model SUPER ALD Exploiter200SP;

[0043] Tantalum source t-butylamine methylethylamine tantalum was purchased from Shenzhen Yuansu Optoelectronics Technology Co., Ltd. with a purity of 99.9%;

[0044] The carbon cloth containing vertical graphene was purchased from Hangzhou Zhehe Instrument Technology Co., Ltd. with a size of 1 cm×1 cm.

[0045] Example 1

[0046] (1) Ta2O5 is deposited on the surface of carbon cloth containing vertical graphene using an atomic layer deposition device to obtain a composite material of vertical graphene / Ta2O5 supported on carbon cloth.

[0047] (2) As described in step (1), specific parameters of atomic layer deposition are set, the sample stage temperature in the atomic layer deposition equipment is set to 250° C., the sample stage preheating time is 35 minutes, the number of cycles is 1, and the residence time of the precursor is 0.5 s. After the deposition is completed, the composite electrode material is obtained.

[0048] The composition of the material was observed by field emission scanning electron microscopy; the components of the composite electrode material were detected by Raman spectroscopy; and the electrochemical performance was determined by an electrochemical workstation.

[0049] Figure 1 This is a SEM image of upright graphene, which mainly shows the unique self-supporting lamellar structure of upright graphene. Figure 2 This is the Raman spectrum of vertical graphene, which mainly shows the obvious 1580cm -1 and 2700cm -1 The characteristic peaks of , correspond to the G peak and the doublet Raman 2D peak of complete phonon dispersion associated with single-layer or few-layer graphene, proving that the sheet is graphene.

[0050] Figure 3 This is the SEM picture of Example 1. It can be seen that it is still a vertical graphene sheet structure, and the sheets are continuous and tight.

[0051] Figure 4 The Raman spectrum of Example 1 shows the -1 、1350cm -1 、1480cm -1 、1580cm -1 、2700cm -1 、2950cm -1 There are 6 Raman peaks at 1140cm -1 Peak and 1480cm -1 The peak is attributed to the sp 2 CC vibration, 1580cm -1 Peak is sp 2 G peak of bonded carbon; 2700cm-1 The peak is the double frequency Raman 2D peak of the complete dispersion of phonons related to single-layer or few-layer graphene; 2950cm -1 The peak is the D+D' peak related to the auxiliary defect expression. Compared with the untreated vertical graphene, the D peak intensity gradually decreases and the half-peak width gradually widens, while the G peak intensity gradually increases and the half-peak width narrows, indicating that the disordered sp 2 The carbon content gradually increases, and the crystallinity and order gradually deteriorate. D / I G The value of decreases, indicating that the internal defects of the material are reduced.

[0052] Figure 5 Figure 2 is the potential window and background current curve of the untreated sample and Example 1. Compared with the untreated sample, the potential window of Example 1 decreased from 3.73 V to 3.69 V, and the background current decreased from -90.45 mA / cm 2 Down to -69.9mA / cm 2 .

[0053] Figure 6 The cyclic voltammetry curves of the untreated sample and Example 1 show that the electrochemical active area of ​​Example 1 is significantly improved from 304 μC / cm 2 Increased to 4995μC / cm 2 , which increased by 16.4 times. This shows that loading Ta2O5 on the surface of vertical graphene can significantly improve its electrochemical performance.

[0054] Example 2

[0055] (1) Ta2O5 is deposited on the surface of carbon cloth containing vertical graphene using an atomic layer deposition device to obtain a composite material of vertical graphene / Ta2O5 supported on carbon cloth.

[0056] (2) As described in step (1), the specific parameters of atomic layer deposition are set, the sample stage temperature in the atomic layer deposition equipment is set to 250° C., the sample stage preheating time is 35 minutes, the number of cycles is 10 times, and the residence time of the precursor is 0.5 s. After the deposition is completed, the composite electrode material is obtained.

[0057] The composition of the material was observed by field emission scanning electron microscopy; the components of the composite electrode material were detected by Raman spectroscopy; and the electrochemical performance was determined by an electrochemical workstation.

[0058] Figure 7 This is the SEM picture of Example 2. It can be seen that it is still a vertical graphene sheet structure, and the sheets are continuous and tight.

[0059] Figure 8 The Raman spectrum of Example 2 shows the-1 、1580cm -1 、1620cm -1 、2700cm -1 、2950cm -1 There are five Raman peaks at 1580cm -1 Peak is sp 2 G peak of bonded carbon; 1620cm -1 The peak related to graphene is 2700cm -1 It is the double frequency Raman 2D peak of complete dispersion of phonons related to single-layer or few-layer graphene; 2950cm -1 The peak is the D+D' peak related to the auxiliary defect expression. Compared with the untreated vertical graphene, the structural change is not obvious, indicating that the material under this condition is mainly SP 2 Mainly carbon.

[0060] Fig. 9 Figure 2 is the potential window and background current curve of the untreated sample and Example 2. Compared with the untreated sample, the potential window of Example 2 decreased from 3.73 V to 3.52 V, and the background current decreased from -90.45 mA / cm 2 Down to -89.75mA / cm 2 .

[0061] Fig.10 The cyclic voltammetry curves of the untreated sample and Example 2 show that the electrochemical active area of ​​Example 2 is significantly improved from 304 μC / cm 2 Increased to 6771μC / cm 2 , which increased by 22.2 times. This shows that loading Ta2O5 on the surface of vertical graphene can significantly improve its electrochemical performance.

[0062] Example 3

[0063] (1) Ta2O5 is deposited on the surface of carbon cloth containing vertical graphene using an atomic layer deposition device to obtain a composite material of vertical graphene / Ta2O5 supported on carbon cloth.

[0064] (2) As described in step (1), the specific parameters of atomic layer deposition are set, the sample stage temperature in the atomic layer deposition equipment is set to 250° C., the sample stage preheating time is 35 minutes, the number of cycles is 20 times, and the residence time of the precursor is 0.5 s. After the deposition is completed, the composite electrode material is obtained.

[0065] The composition of the material was observed by field emission scanning electron microscopy; the components of the composite electrode material were detected by Raman spectroscopy; and the electrochemical performance was determined by an electrochemical workstation.

[0066] Fig.11This is the SEM picture of Example 3. It can be seen that it is still a vertical graphene sheet structure, and the sheets are continuous and tight.

[0067] Fig.12 The Raman spectrum of Example 3 shows the -1 、1580cm -1 、1620cm -1 、2700cm -1 、2950cm -1 There are five Raman peaks at 1580cm -1 Peak is sp 2 G peak of bonded carbon; 1620cm -1 The peak related to graphene is 2700cm -1 It is the double frequency Raman 2D peak of complete dispersion of phonons related to single-layer or few-layer graphene; 2950cm -1 The peak is the D+D' peak related to the auxiliary defect expression. Compared with the untreated vertical graphene, the structural change is not obvious, indicating that the material under this condition is mainly SP 2 Mainly carbon.

[0068] Fig.13 : The potential window and background current curves of the untreated sample and Example 3. Compared with the untreated sample, the potential window of Example 3 decreased from 3.73V to 3.62V, and the background current decreased from -90.45mA / cm 2 Down to -65.93mA / cm 2 .

[0069] Fig.14 The cyclic voltammetry curves of the untreated sample and Example 3 show that the electrochemical active area of ​​Example 3 is significantly improved from 304 μC / cm 2 Increased to 4567μC / cm 2 , which increased by 15.0 times. This shows that loading Ta2O5 on the surface of vertical graphene can significantly improve its electrochemical performance.

[0070] Example 4

[0071] (1) Ta2O5 is deposited on the surface of carbon cloth containing vertical graphene using an atomic layer deposition device to obtain a composite material of vertical graphene / Ta2O5 supported on carbon cloth.

[0072] (2) As described in step (1), the specific parameters of atomic layer deposition are set, the sample stage temperature in the atomic layer deposition equipment is set to 250° C., the sample stage preheating time is 35 minutes, the number of cycles is 30 times, and the residence time of the precursor is 0.5 s. After the deposition is completed, the composite electrode material is obtained.

[0073] The composition of the material was observed by field emission scanning electron microscopy; the components of the composite electrode material were detected by Raman spectroscopy; and the electrochemical performance was determined by an electrochemical workstation.

[0074] Fig.15 This is the SEM picture of Example 4. It can be seen that it is still a vertical graphene sheet structure, and the sheets are continuous and tight.

[0075] Fig.16 The Raman spectrum of Example 4 shows the -1 、1580cm -1 、1620cm -1 、2700cm -1 、2950cm -1 There are five Raman peaks at 1580cm -1 Peak is sp 2 G peak of bonded carbon; 1620cm -1 The peak related to graphene is 2700cm -1 It is the double frequency Raman 2D peak of complete dispersion of phonons related to single-layer or few-layer graphene; 2950cm -1 The peak is the D+D' peak related to the auxiliary defect expression. Compared with the untreated vertical graphene, the structural change is not obvious, indicating that the material under this condition is mainly SP 2 Mainly carbon.

[0076] Fig.17 : The potential window and background current curves of the untreated sample and Example 4. Compared with the untreated sample, the potential window of Example 1 decreased from 3.73 V to 3.62 V, and the background current decreased from -90.45 mA / cm 2 Down to -62.22mA / cm 2 .

[0077] Fig.18 The cyclic voltammetry curves of the untreated sample and Example 4 show that the electrochemical active area of ​​Example 4 is significantly improved from 304 μC / cm 2 Increased to 4589μC / cm 2 , which increased by 15.1 times. This shows that loading Ta2O5 on the surface of vertical graphene can significantly improve its electrochemical performance.

[0078] Example 5

[0079] (1) Ta2O5 is deposited on the surface of carbon cloth containing vertical graphene using an atomic layer deposition device to obtain a composite material of vertical graphene / Ta2O5 supported on carbon cloth.

[0080] (2) As described in step (1), the specific parameters of atomic layer deposition are set, the sample stage temperature in the atomic layer deposition equipment is set to 250° C., the sample stage preheating time is 35 minutes, the number of cycles is 40 times, and the residence time of the precursor is 0.5 s. After the deposition is completed, the composite electrode material is obtained.

[0081] The composition of the material was observed by field emission scanning electron microscopy; the components of the composite electrode material were detected by Raman spectroscopy; and the electrochemical performance was determined by an electrochemical workstation.

[0082] Fig.19 This is the SEM picture of Example 5. It can be seen that it is still a vertical graphene sheet structure, and the sheets are continuous and tight.

[0083] Fig. 20 The Raman spectrum of Example 5 shows the -1 、1580cm -1 、1620cm -1 、2700cm -1 、2950cm -1 There are five Raman peaks at 1580cm -1 Peak is sp 2 G peak of bonded carbon; 1620cm -1 The peak related to graphene is 2700cm -1 It is the double frequency Raman 2D peak of complete dispersion of phonons related to single-layer or few-layer graphene; 2950cm -1 The peak is the D+D' peak related to the auxiliary defect expression. Compared with the untreated vertical graphene, the structural change is not obvious, indicating that the material under this condition is mainly SP 2 Mainly carbon.

[0084] Fig.21 : The potential window and background current curves of the untreated sample and Example 5. Compared with the untreated sample, the potential window of Example 5 decreased from 3.73V to 3.65V, and the background current decreased from -90.45mA / cm 2 Down to -63.12mA / cm 2 .

[0085] Fig. 22 The cyclic voltammetry curves of the untreated sample and Example 5 show that the electrochemical active area of ​​Example 5 is significantly improved from 304 μC / cm 2 Increased to 4657μC / cm 2 , which increased by 15.3 times. This shows that loading Ta2O5 on the surface of vertical graphene can significantly improve its electrochemical performance.

Claims

1. A carbon cloth-supported vertical graphene / Ta2O5 composite electrode, characterized in that: It is obtained by depositing Ta2O5 on the surface of carbon cloth containing vertical graphene using atomic layer deposition equipment.

2. The method for preparing the carbon cloth-supported vertical graphene / Ta2O5 composite electrode according to claim 1, characterized in that: The preparation method is as follows: The carbon containing upright graphene is arranged on the sample stage of the atomic layer deposition equipment, the sample stage temperature is set to 250°C, and the sample stage preheating time is 35 minutes; the number of atomic layer deposition cycles is 1 to 40 times, and the residence time of the precursor tantalum source is 0.5s each time; the composite electrode material is obtained after the deposition is completed.

3. The method for preparing the carbon cloth-supported vertical graphene / Ta2O5 composite electrode as claimed in claim 2, characterized in that: The precursor tantalum source is tantalum methylethylamine.